Implementación de circuitos de comunicación y pruebas de motores ac para el módulo de labvolt 3806-42 en el laboratorio de ingeniería en electricidad de la universidad técnica de Cotopaxi. - Villamarin Álvarez, Silvio Tobías (2019)
The development of the present technological proposal includes the fundamental principles on the relays operation, as a basic protection system for AC motors. The Technical University of Cotopaxi, in the Electrical Engineering Lab counts with a protections module Labvolt 3806-42. This training module has the disadvantage of not having a data acquisition and visualization system for studying the relay behavior. That is why the present project consists on the implementation of a communication system with USB interface, which will allow the link between the protection module and the computer. This communication system provides an interface with data acquisition, whose software is based on Windows, necessary for the didactic operation of the protection module. The software consists of providing all standard measurements of electrical parameters such as: voltage, current, power, frequency, power factor. This data acquisition and control system allows the visualization of waveforms and phasor analysis. This communication system allows the acquisition and data tabulation, allowing the student to reaffirm the knowledge about the relays operation on the motors.